General features of copper mineralization in the eastern Euphrates, Keban-Elazig area, Turkey - Kalender, L; Hanelci, S (Springer India, 2004)
The copper mineralization at Nalliziyaret Tepe, in Eastern Taurid region of Turkey is a typical example of porphyry-type sulphide deposit hosted by Upper Cretaceous Keban Magmatic rocks. The latter, comprising subvolcanic rocks and plutonic rocks of syeno-monzonitic affinity, intrude Keban metamorphic rocks of Permo-Carboniferous age. Major and trace element geochemistry of the magmatic rocks suggest that these are alkaline in nature and intruded in a volcanic arc environment during late orogenic stage. The sulphide mineralization (pyrite, chalcopyrite and minor sphalerite, galena and bornite) in the form of disseminations and stockwork ore veinlets occur in radial fractures of the syenite porphyry pluton. This study envisages two stages of hydrothermal wall-rock alteration during the mineralization. The first stage resulted in sodic, calcic, potassic and low sulphidic alterations but this stage accompanies the copper ore body. The second stage is mainly a sodic alteration that laterally grades into chloritic alteration zones. Fluid inclusion studies in quartz, calcite and fluorite minerals associated with mineralization indicate that the ore forming fluids contain NaCl-CaCl2-MgCl2-FeCl2. The salinity and temperature of mineralization are high during the deposition of the ore minerals and decreased towards the later phases. The fluid inclusions are interpreted here as of two different origins, the early phase representing magmatic origin and the later phase may be of meteoric (shallow) origin. It is concluded here that the copper bearing fluids derived from magmatic rocks circulated through the metamorphic basement and deposited along fractures in the altered syenitic rocks.
Keywords: copper mineralisation; porphyry type; syenites; monzonites; fluid inclusions; Keban-Elazig; Turkey